Plant Breeding Supporting the Sustainable Field Crop Production (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aims to highlight how plant breeding could contribute to strengthening sustainability in field crop production by integrating the application of modern technologies and tools. This Reprint contains eleven articles focusing on the most recent topic of plant breeding.